Philo of Alexandrias Views of the Physical World - Anderson, Charles A. (Mohr Siebeck, 2011)
Philo von Alexandriens Ansichten der wirklich wahrnehmbaren Welt.
PublicationDate: 20110809
Keywords: Judaism -- Cosmology -- Philo -- Nature -- Altes Testament -- Antike -- Antike Philosophie -- Array